(untitled) (Globalization and Business, 2018)
The global financial crisis has brought a new impulse to the discussion of the problem of economic crisis. Economists have divided into two groups - one group believes the main reason for the crisis is the failure of economic theory. The sec- ond group thinks that economists have not been charged in the formation of economic crisis. The most problematic aspect of the economic crisis is their prediction. Mainstream neoclassical economic theory completely excludes the possibility of predicting crises. In the analysis of this issue, we use the concepts: “point prediction”, “prediction corridor”, “stationary regime” of economy functioning, and N. Kondratiev’s Great Cycles Con- junction Theory. There is possible to define the “prediction’s corridors” within the stationary regimes of economy functioning. In these periods the economy is characterized with high quali- ty of volatility. By observing the main economic indicators in these periods, we think, it is possible to predict the approxi- mate date of the economic crisis.